-9x+22+11x+21=2

Simple and best practice solution for -9x+22+11x+21=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x+22+11x+21=2 equation:


Simplifying
-9x + 22 + 11x + 21 = 2

Reorder the terms:
22 + 21 + -9x + 11x = 2

Combine like terms: 22 + 21 = 43
43 + -9x + 11x = 2

Combine like terms: -9x + 11x = 2x
43 + 2x = 2

Solving
43 + 2x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-43' to each side of the equation.
43 + -43 + 2x = 2 + -43

Combine like terms: 43 + -43 = 0
0 + 2x = 2 + -43
2x = 2 + -43

Combine like terms: 2 + -43 = -41
2x = -41

Divide each side by '2'.
x = -20.5

Simplifying
x = -20.5

See similar equations:

| 5cx-d=ax+b | | 5x+5=2x+23 | | 22t^4+18t^2-11t^6=0 | | -6=-2/3y | | 3x+18=-3x-6 | | 6n+11-8n=22 | | X^3-1/X^3=14 | | 7=8(x+5)+5 | | 3.4a=7.004 | | 1=1/3x^2 | | 5(11-3x)+4(2x+1)=3 | | 7(x+4)-(3x-1)=8 | | (3x+4)=5x | | y=ctg(1-2x) | | y=ctg(1-2xz) | | 2+2+3=3 | | (12x+20)+(7x)+(20x-35)=180 | | 6=6(x+5)-2x | | (3x+7)=(5x-3) | | 14=x*26 | | 2(x+7)+6=26 | | (5x-1)=(6x-3) | | 2=5(x+9)8x | | T=p-ir | | 4a^2-147=a^2 | | (y-2)-(y+1)=(y-3)-2 | | y=arcsen(3x) | | -(2x+5)=-21 | | 5/8m=60 | | 7-6/5x=8 | | 2(n)+5=45 | | 3x+1-2=7-2 |

Equations solver categories